Electronic Commerce Aplications: Pentingnya Aplikasi e-commerce di Dunia Modern dan Dampaknya terhadap Operasi Bisnis - Yoerdan, Gebrilla; Al Amin, Muhammad Fadhil (Jurnal Pustaka Manajemen (Pusat Akses Kajian Manajemen), 2025)
The development of electronic commerce (e-commerce) has brought fundamental changes to the way businesses operate in the digital era. Advances in information technology, increased internet penetration, and the growth of digital payment systems have positioned e-commerce as one of the main pillars of modern business strategies. This study aims to examine the significance of e-commerce applications in the modern world and their impact on business operations. The method employed is a literature review, analyzing various relevant scientific sources to identify concepts, benefits, challenges, and implications of e-commerce implementation. The findings indicate that e-commerce plays a crucial role in improving operational efficiency, expanding market reach, increasing sales and revenue, strengthening digital marketing strategies, and enhancing supply chain manage ment. In addition, e- commerce enables data-driven decision making and enhances competitiveness, particularly for small and medium - sized enterprises. However, the implementation of e-commerce also faces challenges such as intense competition, data security risks, and the potential for online fraud. Therefore, businesses are required to continuously adapt and develop appropriate strategies to optimize the utilization of e-commerce in a sustainable manner.